Combining Microstructured Surface and Mesh Covering for Heat Transfer Enhancement in Falling Films of Refrigerant Mixture - Oleg Volodin; Nikolay Pecherkin; Aleksandr Pavlenko (Energies, 2023)
The article presents the experimental results of combining a basic microstructure with partly closed pores and a mesh covering for heat transfer enhancement at the film flow of a refrigerant mixture. To reveal the effect of the combined structure, heat transfer on a microstructured surface without a covering as well as on a smooth surface with a mesh covering only has been studied. All experimental series were carried out using a binary mixture of R114 and R21 refrigerants. The mixture film flowed down the outer surface of a vertical cylinder in the undeveloped turbulence regime, when the film Reynolds number varied from 400 to 1300. It is shown that a microstructured surface with a fin pitch of 200 μm, fin height of 220 μm, and longitudinal knurling pitch of 160 μm, created by deformational cutting, demonstrates significant heat transfer enhancement: up to four times as compared to a smooth surface. However, adding a mesh covering with an aperture of 220 μm and a wire diameter of 100 μm reduces the intensification. The mesh covering overlaid on a smooth surface also does not provide heat transfer enhancement as compared to the smooth surface itself. The absence or even deterioration of heat transfer enhancement on surfaces with mesh covering can be primarily associated with the low thermal conductivity of the mesh material and shortcomings of the applied method of mesh mounting. The possibility of deteriorating vapor removal due to the incorrect selection of mesh covering parameters was also analyzed. The heat transfer coefficient values obtained for basic microstructured surfaces were compared with the dependencies available in the literature for predicting pool boiling heat transfer on microfinned surfaces.